2021
DOI: 10.1038/s41467-021-22027-0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of stimulus-independent and task-unrelated thought from functional brain networks

Abstract: Neural substrates of “mind wandering” have been widely reported, yet experiments have varied in their contexts and their definitions of this psychological phenomenon, limiting generalizability. We aimed to develop and test the generalizability, specificity, and clinical relevance of a functional brain network-based marker for a well-defined feature of mind wandering—stimulus-independent, task-unrelated thought (SITUT). Combining functional MRI (fMRI) with online experience sampling in healthy adults, we define… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 124 publications
4
49
1
Order By: Relevance
“…This work, to our knowledge, is the first study to utilize a machine learning approach and whole-brain functional connectivity to predict individual response time variability as an avenue to study brain correlates of mind-wandering in healthy older adults. Our results are consistent with the emerging literature demonstrating that machine learning approaches, particularly the CPM framework, can be utilized to predict individual cognitive outcomes from functional connectivity ( Avery et al, 2020 ; Feng et al, 2019 ; Finn et al, 2015 ; Gao et al, 2020 ; Jangraw et al, 2018 ; Kucyi et al, 2021 ; Rosenberg et al, 2016 ). The finding that rest-FC variance solely did not predict RT_CV is consistent with prior CPM work demonstrating that predictive utility is suboptimal when brain-based models of individual cognitive measures are trained on resting-state functional connectivity ( Greene et al, 2018 ; Jiang et al, 2020 ; Tomasi and Volkow, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This work, to our knowledge, is the first study to utilize a machine learning approach and whole-brain functional connectivity to predict individual response time variability as an avenue to study brain correlates of mind-wandering in healthy older adults. Our results are consistent with the emerging literature demonstrating that machine learning approaches, particularly the CPM framework, can be utilized to predict individual cognitive outcomes from functional connectivity ( Avery et al, 2020 ; Feng et al, 2019 ; Finn et al, 2015 ; Gao et al, 2020 ; Jangraw et al, 2018 ; Kucyi et al, 2021 ; Rosenberg et al, 2016 ). The finding that rest-FC variance solely did not predict RT_CV is consistent with prior CPM work demonstrating that predictive utility is suboptimal when brain-based models of individual cognitive measures are trained on resting-state functional connectivity ( Greene et al, 2018 ; Jiang et al, 2020 ; Tomasi and Volkow, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…Using whole brain, task-based, or resting state functional connectivity, several recent studies have demonstrated the utility of the CPM technique in identifying individual differences in brain functional architecture. These have allowed for the construction of brain-based models capable of predicting fluid intelligence ( Finn et al, 2015 ), processing speed ( Gao et al, 2020 ), attention ( Rosenberg et al, 2016 ), reading ability ( Jangraw et al, 2018 ), working memory ( Avery et al, 2020 ; Manglani et al, 2021 ), loneliness ( Feng et al, 2019 ), mind-wandering ( Kucyi et al, 2021 ), or even diseased states such as Alzheimer’s disease ( Lin et al, 2018 ) and attention deficit hyperactivity disorder (ADHD; Barron et al, 2020 ). A recent fMRI study demonstrated the utility of CPM to build generalizable models of mind-wandering, as measured using an experience sampling method, in healthy young adults and adults with ADHD ( Kucyi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, LFPN-DMN segregation may not always be adaptive. Mounting evidence suggests that engagement of both the LFPN and DMN is actually beneficial when performing certain kinds of tasks, especially those on which intentional mind-wandering is helpful, such as mentalizing or creative thinking ( Christoff et al, 2009 , Dixon et al, 2014 , Kucyi et al, 2021 ). Indeed, engaging in deliberate mind-wandering—argued to be distinct from uncontrolled mind-wandering—is thought to help fuel creative insights ( Agnoli et al, 2018 ) and be associated with less reactive emotional processing ( Seli et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Task-related fMRI studies have shown that stronger activation of the LFPN and stronger deactivation of the DMN is associated with better performance on tasks that require focus on externally presented stimuli (Weissman et al, 2006). On the other hand, engagement of both the LFPN and DMN is beneficial when performing tasks on which intentional mind-wandering is helpful (Christoff et al, 2009; Dixon et al, 2014; Kucyi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%